2018
DOI: 10.5958/0976-5506.2018.00490.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Methanolic Fruit Extract of Citrus aurantifolia Using Gas Chromatography-Mass Spectrum and FT-IR Techniques and Evaluation of Its Anti-bacterial Activity

Abstract: The objectives of this study were analysis of the secondary metabolite products and evaluation antibacterial and antifungal activity. Bioactives are chemical compounds often referred to as secondary metabolites. Twenty nine bioactive compounds were identified in the methanolic extract of Citrus aurantifolia. The identification of bioactive chemical compounds is based on the peak area, retention time molecular weight and molecular formula. GC-MS analysis of Citrus aurantifolia revealed the existence of the Thie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Major compounds in methanol and hexane extracts like presilphiperfolan-1-ol [ 32 ], nalidixic acid [ 33 ], phytol [ 34 ], gamma-sitosterol [ 35 ], α-amyrin [ 36 ] are reported to be antibacterial/anti-fungal along with other properties. It has been reported that heptatriacontanol gives the antimicrobial activity to methanol extract of Trilepisium madagascariense [ 37 ] and cholestan-3-ol, 2-methylene-, is the compound present in the antibacterial fraction of Z.officianale [ 38 ] and Citrus aurantifolia1 [ 39 ] These compounds were identified from the hexane extract of O. thymiflorus . The antibacterial, anti fungal activity of the compounds detected from the extract justify the use of the plant in traditional medicine against skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Major compounds in methanol and hexane extracts like presilphiperfolan-1-ol [ 32 ], nalidixic acid [ 33 ], phytol [ 34 ], gamma-sitosterol [ 35 ], α-amyrin [ 36 ] are reported to be antibacterial/anti-fungal along with other properties. It has been reported that heptatriacontanol gives the antimicrobial activity to methanol extract of Trilepisium madagascariense [ 37 ] and cholestan-3-ol, 2-methylene-, is the compound present in the antibacterial fraction of Z.officianale [ 38 ] and Citrus aurantifolia1 [ 39 ] These compounds were identified from the hexane extract of O. thymiflorus . The antibacterial, anti fungal activity of the compounds detected from the extract justify the use of the plant in traditional medicine against skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Very interestingly, 2-vinyl-9-[beta-D-ribofuranosyl] hypoxanthine was detected in ethyl acetate extract of Rhizopus oryzae. It has previously been reported from the methanolic fruit extract of Citrus aurantifolia [39]. Production of bioactive compounds in endophytic organisms can be linked with the medicinal properties of plants, and plants may have a role in initiating production of these metabolites due to specific environment offered to fungal strains [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on EPEC revealed induced rearrangements of the cytoskeleton, which have begun to provide various conclusions. The mechanisms involved in the appearance of such a phenomenon used by this pathogen were to undermine the host cell cytoskeleton and signaling pathways [9,24] .…”
Section: Discussionmentioning
confidence: 99%